An Integrated Overview of Rasendra Chudamani (International Journal of Ayurveda and Pharma Research, 2024)
Rasashastra is an important branch of Ayurveda which deal with the formulation and preparation of various mineral and metal preparations. Rasendra Churamani is one of the important ancient texts written by Acharya Somadeva in 12' AD. Hindi commentary of this book is available, written by Arthabodhini Hindi Teekakar Vaidya Pravara, Rasagya Pandit Shree Rameshwar Dayal Bajpeyee.  In this classical text detailed knowledge of Rasa, Rasashala Nirman Vidhi, collection and storage in specific direction, terminologies to understand the Rasa karma, various type of Musa, Puta, Rasa-Aushadhi, Parada specific Samskar, Bhasma preparation by various mineral, metals, Maharasa, Uprasa, Sadharan Rasa are given. Rasendra Chudamani containing the experiences of previous authors. In ancient time, it has a great contrition in pharmaceutical science, by its process like Bhasma Nirmana, Satva Nirmana and purification methods of metals and minerals drugs.